Pengaruh Profesionalisme Dan Media Pendidikan Terhadap Prestasi Belajar Siswa Di Sma Negeri 10 Kota Jambi - Pratiwi Indah Sari (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2017)
The purpose of this research is to describe the extent of the influence and relationship education terhaadap media professionalism and student achievement in SMAN 9 Jambi. The population in this study amounted to 662 people with the withdrawal by proportional random sampling, the sample was 87. Based on the results, it can be concluded that with the professionalism of the teachers and the ability to use educational media in the learning process will facilitate the students receive the material presented and will increase student achievement itself directly.